Informal carers of people with dementia - Rihter, Liljana (Metodološki zvezki, 2023)
Social work is constantly evolving and theoretically enriched to meet people's needs in new social situations. Informal carers must balance care with other demands while facing a range of obstacles. Despite research on what informal carers require, a specific typology of their needs has yet to be formulated. The research question considered is "What are the (groups of) needs of individuals who provide informal care for people with dementia?". As part of the research project Long-term Care for People with Dementia in Social Work Theory and Practice, we interviewed a non-random convenience sample of 20 relatives acting as informal carers of people with dementia. The results are presented as a typology of needs on the micro level (personal health—emotional health, physical health), mezzo level (care tasks—support from formal care, planning—information, counselling) and macro level (legislation, system changes). Most obstacles and needs identified were on the micro and mezzo levels. More than on the system (macro level), informal carers see the responsibility and burden of care as lying on the individual (micro level) and institutions and the community (mezzo level).
Keywords: caregiving task; dolgotrajna oskrba; informal care; long-term care; neformalna pomoč; osebno zdravje; personal health; social work; socialno delo